(untitled) (Journal of the College of Basic Education, 2022)
The first requirementThe linguistic and idiomatic definition of arbitrator and allegorical:ﭽ ﮖ ﮗ ﮘ ﮙ ﮚ ﮛ ﮜ ﮝ ﭼ ﭼ (), ﭽ ﭩ ﭪ ﭫ ﭭ ﭮ ﭯ ﭰ ﭱ ﭲ ﭳ ﭵ ﭵ ﭶ ﭷ ﭹ ﭺﭼ ﭺﭼ (), ﭽ ﮘ ﮙ ﮛ ﮝ ﮞ ﮟ ﮠ ﮡ ﮢ ﮢ ﮢ ﮢ ﮢ ﮢ ﮢ ﮢ ﮢ ﮣﮤﭼ.( )Allamah Tabatabaei says: (We see in the first verse that it states that the whole of the Qur’an is decisive, and you mean that it is fixed and that no defect or invalidity enters into it. And the second verse states that the whole of the Qur’an is allegorical, and you mean that its verses are on the same frequency in beauty, style, sweetness of tone, and miraculousness. As for The third verse divides the Qur’an into two distinct and similar parts. ( )Al-Zarqani says: (And there is no contradiction between these three releases, because the meaning of all of its rulings is that it is organized, sober, elaborate, and the meaning of all of it is similar, that it resembles each other in its rulings, goodness, and reaching the limit of miraculousness in its words and meanings. Its indication of what God Almighty wants is clear, and from it what is hidden is its indication of this purpose. ( )And that research on the seventh verse of Surat Al-Imran advanced resulted in the emergence of one of the investigations of the sciences of the Qur’an, which is the science of the airtight and the allegorical.